Impact of COVID 19 on outcome of primary percutaneous coronary intervention in Nepal. - Kadel, Arun; Karki, Shova; Rauniyar, Binay Kumar; Kharel, Sushant; Neupane, Keshab Raj; Acharya, Kiran Prasad; Sherpa, Kunjang; Adhikari, Chandra Mani (Nepalese Heart Journal, 2022)
Background and Aims: The COVID 19 pandemic have affected the patients with ST segment elevation myocardial infarction as the number of patients presenting with STEMI declined substantially and those who underwent primary PCI had poor outcome. Our aim was to analyze the in-hospital and 30-days mortality in STEMI undergoing Primary PCI during second wave of COVID 19. Methods: A prospective cohort study was conducted at Shahid Gangalal National Heart Centre, Bansbari, Kathmandu. Convenience sampling of patients who underwent primary PCI were enrolled in this study and were followed up for 30 days. Numerical variables were described as Mean ± Standard Deviation (SD) and categorical variables were described as frequency and percentage. p values were calculated and considered significant if < 0.05. Results: During this study period of 2 months from 1st May 2021 to 30th June 2021, 97 patients with STEMI underwent primary PCI, including 12 (12.47%) COVID 19 positive cases. 30 days mortality was 15.4% including in-hospital mortality of 11.34%. Among COVID 19 positive cases, in-hospital mortality was 33.33% and 30-days mortality was 55.55% which was significantly higher than non COVID 19 patient who underwent primary PCI (P=0.003). Conclusion: Overall, mortality rate of primary PCI during COVID 19 second wave has been increased and mortality of COVID 19 positive patients who underwent primary PCI was significantly higher than non-COVID 19 patients who underwent primary PCI.